2012
DOI: 10.1111/j.1365-3024.2012.01364.x
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic acid signalling in gastrointestinal parasite infections: lessons from mouse models

Abstract: SummaryRetinoic acid or vitamin A is important for an extensive range of biological processes, including immunomodulatory functions, however, its role in gastrointestinal parasite infections is not yet clear. Despite this, parasite infected individuals are often supplemented with vitamin A, given the co-localised prevalence of parasitic infections and vitamin deficiencies. Therefore, it is important to understand the impact of this vitamin on the immune responses to gastrointestinal parasites. Here, we review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 74 publications
0
22
0
1
Order By: Relevance
“…9 In addition, Ascaris worms express a range of retinol binding proteins, retinol dehydrogenases, and retinoic acid receptors, which use retinol for growth and development, 22 although a study in Sri Lanka among adolescent girls found that Trichuris infection but not Ascaris infection was associated with lower serum vitamin A concentration compared with those girls not infected. 23 WHO and United Nations Children's Fund (UNICEF) have recommended that deworming be included in vitamin A supplementation programs, 24 and combined vitamin A supplementation and deworming have been shown to reduce Ascaris reinfection rates among PSC in Panama.…”
Section: Discussionmentioning
confidence: 99%
“…9 In addition, Ascaris worms express a range of retinol binding proteins, retinol dehydrogenases, and retinoic acid receptors, which use retinol for growth and development, 22 although a study in Sri Lanka among adolescent girls found that Trichuris infection but not Ascaris infection was associated with lower serum vitamin A concentration compared with those girls not infected. 23 WHO and United Nations Children's Fund (UNICEF) have recommended that deworming be included in vitamin A supplementation programs, 24 and combined vitamin A supplementation and deworming have been shown to reduce Ascaris reinfection rates among PSC in Panama.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistic understanding of the relationship between infection and nutrient deficiencies is also lacking, but it is likely that reduced appetite, impaired nutrient absorption following helminth‐induced tissue damage and increased nutrient loss all play a role . With regard to vitamin A deficiencies, helminths including Ascaris lumbricoides express retinol and retinoic acid‐binding and degrading proteins that they utilize for their growth and development . Retinoic acid is highly enriched in the gastrointestinal tract and is key to a functioning adaptive immune system .…”
Section: Ilc2 and Nutrient Sensingmentioning
confidence: 99%
“…Anti-inflammatory (Thielitz et al, 2006;Andrea and Zaenglein, 2008), antifungal and antimicrobial effects of RA has also been observed against several fungi and bacteria (Mikhlin et al, 1983). RA antiparasitic activity was rarely investigated (Hurst and Else, 2012). For instance, RA was correlated with successful clearing of Trichinella.…”
Section: Cystic Echinococcosis (Ce) Is a Chronic Zoonosis Caused By Tmentioning
confidence: 99%